Tinjauan Manajemen Modal Kerja: Analisis Bibliometrik dan Prospek Masa Depan - Khoirotut Tamami; Surya Raharja (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - The aim of the research is to analyze trends, patterns, and future directions of working capital management using a bibliometric approach. Method - This study employed a bibliometric analysis method utilizing publications obtained from the Scopus database. The search process was conducted based on keywords, field of study, document type, language, and open access, resulting in 88 final publications for analysis. Main Findings - Research on working capital management continues to grow, focusing on business and management, economics, econometrics, and finance. Developing countries like Indonesia and China are leading research contributions, while developed countries like France, Canada, and others are making new contributions. Theory and Practical Implications - Theoretically, this research enriches academic understanding of the evolution of working capital management studies through a bibliometric approach. Practically, it provides direction for academics, practitioners, and policymakers to develop evidence-based, collaborative, and contextualized working capital management strategies addressing global change. Novelty - The novelty of this research lies in the use of bibliometric analysis to comprehensively map the trends, patterns, and directions of global development of working capital management research in the 2009–2025 time period, which has not previously been widely done in financial studies.